THE EFFECT OF PROBIOTIC ON IMMUNITY IMPROVEMENT IN THE FRY AND SPAWNER PRODUCTION OF PACIFIC WHITE SHRIMP Litopenaeus vannamei - Haryanti Haryanti; Ahmad Muzaki; Sari Budi Moria Sembiring; Fahrudin Fahrudin; I Gusti Ngurah Permana; Ida Komang Wardana (Indonesian Aquaculture Journal, 2014)
In order to improve immune system of Pacific white shrimp L. vannamei from any kinds of diseases, various probiotic agents were tested such as Bacillus sp. BC, Alteromonas sp. BY-9 and mixed of both. The probiotics were cultured and added directly to the larval rearing tank (106 cfu/mL equal to 0.5 liter/m3) up to PL-12. In cultured shrimp spawners, probiotic was mixed with feed coated with chitosan, and without adding probiotic as control. In the present experiment, shrimp fry and spawners were reared in tank capacity of 5 m3 and 8 m3. Immunity response was analyzed by quantitative value of the immunity related gene expression with RTqPCR. The results showed that survival rate of shrimp fry cultured with mixed probiotic was 63.16% (PL-8) and 53.46% (PL-12), while control 13.35% (PL-8) and 12.48% (PL-12) respectively. The number of shrimp hemocytes starting from 420 to 530.5 x 104 cells/mL and after challenged with WSSV (for 72 hrs exposure) between two treatments of Alteromonas sp. BY-9 and Bacillus cereus BC was not significantly different P>0.05 (402.5 and 432.5 x 104 cells/mL), while in mixed probiotic and control treatments were 391.75 and 229.0 x 104 cells/mL, respectively. The analysis of immunity gene expression revealed that the use of probiotic from larval stages up to spawner has been proved in increasing immunity responses quantified from ProPO activating system (prophenoloxidase/proPO) as much as 1.6-2.0 fold, clotting system (transglutaminase, clotting protein) of 1.5-2 fold, Antimicrobial Peptide System (anti-LPS factor, crustin, lysozyme, penaiedin2) of 1.5-2.8 fold, and Antioxidant defense mechanism (superoxidase dismutase/SOD, glutathione peroxidase/GPx) of 1.8-2.0 fold compared to control.